Hydrogen Absorption and Self-Corrosion of Mg Anode: Influence of Aqueous Electrolyte Species - Andrei Nazarov; Tatiana Yurasova; Andrey Marshakov (Corrosion and Materials Degradation)
This review examines the impact of various aqueous electrolytes on hydrogen absorption and self-corrosion in magnesium (Mg) anodes. The discussion integrates both historical and recent studies to explore the mechanisms behind self-corrosion and anomalous hydrogen evolution (HE) under conditions of the Negative Difference Effect (NDE) and Positive Difference Effect (PDE). The focus is on the formation and oxidation of magnesium hydride in regions of active dissolution under NDE conditions. In the case of PDE, anodic dissolution occurs through the passive MgO-Mg(OH)₂ film, which shields the metal from aqueous electrolytes, thereby reducing hydrogen absorption and abnormal HE. The NDE conditions showed delayed reduction activity at the surface, attributed to a hydride phase within the corrosion product layer. Hydride ions were quantified through their anodic oxidation in an alkaline electrolyte, measured by the electric charge passed. The review also considers the role of de-passivating halide ions, electrolyte acidity buffering, and the addition of ligands that form stable complexes with Mg2⁺ ions, on the rates of hydride formation, self-corrosion, and anodic dissolution of Mg. The study evaluates species that either inhibit or promote hydrogen absorption and self-corrosion.